The Stress and Adversity Inventory for Adults (Adult STRAIN) in Korean: Initial Validation and Associations with Psychiatric Disorders - Eun Soo Kim; Yun Tae Kim; Kang-Seob Oh; Young Chul Shin; Sang-Won Jeon; Dong-Won Shin; Sung Joon Cho; George M. Slavich; Junhyung Kim (Brain Sciences)
Background/Objectives: Stressors occurring across the life course are considered to have a cumulative impact on health, but there is no instrument for assessing lifetime stressor exposure in Korea. Therefore, we validated the Stress and Adversity Inventory (Adult STRAIN) in Korean. Methods: We translated the Adult STRAIN into Korean and examined its concurrent, predictive, and comparative predictive validity in 218 Korean adults (79 men, 139 women; Mage = 29.5; 19–50 years old) recruited from a psychiatric setting. We assessed concurrent validity using Pearson’s correlations, predictive validity using multiple regression models, and comparative predictive validity using multivariate logistic regression to identify participants with lifetime psychiatric diagnoses. Results: The Korean STRAIN exhibited sufficient usability and acceptability; good concurrent validity with other measures of early adversity, life events, and perceived stress (rs = 0.48–0.61); and strong predictive validity in relation to anxiety and depressive symptoms (β = 0.08–0.47; ΔR2 = 0.11–0.21). Each domain of Korean-style stress, based on the timing, type, life domain, and sociopsychological characteristics of stress exposure, showed a different distribution of lifetime psychiatric diagnosis probabilities (odds ratios = 1.20–4.85). Finally, the test–retest reliability for total lifetime stressor count and severity over four weeks was high. Conclusions: The Korean STRAIN is a practical, valid, and reliable instrument for researchers and clinicians to efficiently assess lifetime stressor exposure.